ER stress-induced secretion of proteins and their extracellular functions in the heart - Meyer, Bianca A.; Doroudgar, Shirin (Cells, 2020)
Endoplasmic reticulum (ER) stress is a result of conditions that imbalance protein homeostasis or proteostasis at the ER, for example ischemia, and is a common event in various human pathologies, including the diseased heart. Cardiac integrity and function depend on the active secretion of mature proteins from a variety of cell types in the heart, a process that requires an intact ER environment for efficient protein folding and trafficking to the secretory pathway. As a consequence of ER stress, most protein secretion by the ER secretory pathway is decreased. Strikingly, there is a select group of proteins that are secreted in greater quantities during ER stress. ER stress resulting from the dysregulation of ER Ca2+ levels, for instance, stimulates the secretion of Ca2+-binding ER chaperones, especially GRP78, GRP94, calreticulin, and mesencephalic astrocyte-derived neurotrophic factor (MANF), which play a multitude of roles outside the cell, strongly depending on the cell type and tissue. Here we review current insights in ER stress-induced secretion of proteins, particularly from the heart, and highlight the extracellular functions of these proteins, ranging from the augmentation of cardiac cell viability to the modulation of pro- and anti-apoptotic, oncogenic, and immune-stimulatory cell signaling, cell invasion, extracellular proteostasis, and more. Many of the roles of ER stress-induced protein secretion remain to be explored in the heart. This article is part of a special issue entitled “The Role of Proteostasis Derailment in Cardiac Diseases.”